Diagnosis, Incidence and Extent of Adhesions in Buffaloes with Uterine Torsion at Referral Hospital - Prajapati, R. D.; Chauhan, P. M.; Prajapati, A. S.; Sutaria, P. T.; Vaghasiya, Y. H. (International Journal of Bio-resource and Stress Management, 2024)
The present study was conducted to determine the incidence and extent of uterine adhesions following uterine torsion in Mehsana buffaloes. A total of 109 uterine torsion-affected buffaloes were recorded for treatment during the January, 2020 to December, 2022, and they are included in the present work. All the buffaloes were scanned by per-rectal, trans-abdominal ultrasonography and grossly inspection of the uterus during the caesarean section for the presence of adhesions and its nature of extensiveness to the uterus. The uterine adhesions through ultrasonography were predicted by the presence of fibrin bands and absent of anechoic fluid between the omentum and uterine serosa layer. Grossly, the extent of the uterine adhesions was classified as either localized or widespread type flimsy to dense in nature during the caesarean operation. The intra-operative in-situ detorsion was achieved in buffaloes with flimsy type uterine adhesions. The overall incidence of adhesions was recorded to be 29.36%. Among them, the incidence of localized type was observed in 21 buffaloes (65.62%) and widespread variety in 11 buffaloes (34.38%), either flimsy or dense. The majority of adhesions were found between the uterus and the inner omental layer. It is concluded that the incidence of uterine adhesions in uterine torsion-affected buffaloes was reported to be 29.36% using different techniques to identify the localized to widespread uterine adhesions. Further, ultrasonography can be helpful in the prediction and early detection of uterine adhesion in buffaloes with uterine torsion, which helps in better obstetrical management.